Gestão de espaços físicos e serviços de saúde - proposta de um manual operacional de gestão de espaço para aquisição e instalação de equipamentos no Departamento de Oftalmologia e Ciências Visuais da Universidade Federal de São Paulo - Souza, Rodrigo Mariano De [UNIFESP] (2021)
This research aims at the management of physical spaces as part of the planning and organizational development process, having as reference the equipment installation and installation process at Universidade Federal de São Paulo - UNIFESP, teaching, research and health care activities that require the integration of services, and updating technologies. The growing flows of activities in the population and participation in training and assistance impacted on the physical space, what is the main material of service resource, what is the quality associated with the competence of the professionals, the available resources and the safe reception of the different audiences. The acquisition of technologies requires technical and sectorial planning decisions that take into account the perspective of institutional development and the management of physical assets, to guarantee the continuous functioning of essential activities and the return on investments in innovations and updates. This study started from the analysis of physical space management procedures of the Department of Ophthalmology and Visual Sciences (DOVS), UNIFESP, in the quadrennium 2015-2018, based on the Institution's purchase and services criteria and management fees. In order to improve this process, apply an Operational Space Management Guide with instructions for procedures for the acquisition and installation of equipment, associating space management studies to ensure viability and economy. The guide presented as Product of this research will be available in physical and electronic format to DOVS, followed, and other departments of the University.